Answer:
The new equation is [tex]h(x)=4(x-7)^2-19[/tex]
Step-by-step explanation:
Given : Function [tex]g(x) = 4x^2 - 16[/tex] were shifted 7 units to the right and 3 down.
To find : What would the new equation be?
Solution :
Shifting to the right with 'a' unit is
f(x)→f(x-a)
So, shifting g(x) 7 units to the right is
[tex]h(x) = 4(x-7)^2-16[/tex]
Shifting to the down with 'b' unit is
f(x)→f(x)-b
So, shifting g(x) 3 units down is
[tex]h(x)=(4(x-7)^2-16)-3[/tex]
[tex]h(x)=4(x-7)^2-19[/tex]
The new equation is [tex]h(x)=4(x-7)^2-19[/tex]